CLINICODIAGNOSTIC PARALLELS IN ADENOMYOSIS-RELATED INFERTILITY - A. R. Jhigalenko; l. Yu. Karakhalis; N. S. Papova (Кубанский научный медицинский вестник)
Aim. The aim of this study was to determine parallel between clinical manifestations of adenomyosis and imaging methods data.Materials and methods. 247 patients were examined, from which is formed clinical groups: 1st group included 26 patients (35,1%), and 2nd group – 23 patients (31,1%) with adenomyosis-related infertility, 3rd group (control) – 25 patients (33,8%). It has been clarified reproductive anamnesis, estimated clinical course of adenomyosis and performed hysteroscopy, and ultrasound assessment of resistance indexes in uterus vessels, Hatle index, thickness of «transition area» on MRI.Results. The intensity of algomenorrhea, dyspareunia, and pelvic pain outside of menses is correlated with US data: the resistance indexes (RI) of uterus vessels as Hatle index and thickness of «transition area» were significantly higher in groups 1 and 2 than in control (р<0,0001); hypervascularization and the presence of the dark red areas showed high sensitivity and specificity; the correlation coefficient between hysteroscopically signs and visual evaluation scale of pain came to R=0,637.Conclusion. The severity of the adenomyosis clinical intensity is correlated with US, MRI, and hysteroscopy data.